Aftershocks triggered by fluid intrusion: Evidence for the aftershock sequence occurred 2014 in West Bohemia/Vogtland. Issue 4 (12th April 2016) - Hainzl, S.; Fischer, T.; Čermáková, H.; Bachura, M.; Vlček, J.
Abstract: The West Bohemia/Vogtland region, central Europe, is well known for its repeating swarm activity. However, the latest activity in 2014, although spatially overlapping with previous swarm activity, consisted of three classical aftershock sequences triggered by M L 3.5, 4.4, and 3.5 events. To decode the apparent system change from swarm‐type to mainshock‐aftershock characteristics, we have analyzed the details of the major M L 4.4 sequence based on focal mechanisms and relocated earthquake data. Our analysis shows that the mainshock occurred with rotated mechanism in a step over region of the fault plane, unfavorably oriented to the regional stress field. Most of its intense aftershock activity occurred in‐plane with classical characteristics such as (i) the maximum magnitude of the aftershocks is significantly less than the mainshock magnitude and (ii) the decay can be well fitted by the Omori‐Utsu law. However, the absolute number of aftershocks and the fitted Omori‐Utsu c and p parameters are much larger than for typical sequences. By means of the epidemic‐type aftershock sequence model, we show that an additional aseismic source with an exponentially decaying strength triggered a large fraction of the aftershocks. Corresponding pore pressure simulations with an exponentially decreasing flow rate of the fluid source show a good agreement with the observed spatial migration front of the aftershocks extending approximately with log ( t ) . Thus, we conclude that the mainshock opened fluid pathways from a finite fluid source into the fault plane explaining the unusual high rate of aftershocks, the migration patterns, and the exponential decrease of the aseismic signal. Key Points: Three aftershock sequences occurred after 30 years of swarms on the same fault plane Mainshocks activated a fault jog and had oblique mechanisms compared to aftershocks Mainshock‐triggered fluid intrusion explains observed earthquake migration and high activity rates